Literature Review–Based Study on Health Insurance in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This study provides a comprehensive literature-based examination of the present status of the health insurance industry in India, with a focus on key reforms, program performance, financial protection, and systemic challenges. Drawing on evidence from peer-reviewed research, government reports, and national datasets, the review synthesises findings across public schemes (such as RSBY and PM-JAY), private health insurance markets, and mixed public–private models. The analysis shows that while public health insurance has improved access to inpatient services for low-income households, its ability to reduce out-of-pocket expenditure remains limited due to exclusions, inadequate coverage of outpatient care, and provider-related inefficiencies. Private health insurance has expanded rapidly but continues to serve predominantly urban, higher-income groups, with persistent issues of affordability, claim settlement delays, and product complexity. Cross-scheme comparisons highlight fragmentation, low awareness, inequitable coverage, and significant gaps in regulation. The study identifies critical research gaps, including the need for longitudinal assessments of PM-JAY, evaluations of digital claims and TPAs, comparative state-level analyses, and behavioural studies on enrolment and retention. Overall, the findings suggest that India’s health insurance ecosystem is expanding but remains structurally fragmented, requiring strengthened governance, improved benefit design, strategic purchasing, and integrated risk pooling to advance towards Universal Health Coverage.